LEARNING MODEL OF TAHFIDZ-BASED ISLAMIC RELIGIOUS EDUCATION IN TAUD SAQU JEMBER - Huwaida, Hasna'; Fahrany, Sofia (Tahdzib Al-Akhlaq: Jurnal Pendidikan Islam, 2024)
The Qur'an is both light and illumination for all humanity. It acts as a “hudan,” which becomes a lamp in the darkness of a world without knowledge. The Qur'an is the source of all knowledge, including education, as has been exemplified directly by the Prophet Muhammad PBUH. Therefore, Islamic Religious Education directly has a clear principle in its concept and practice, namely the Qur'an. Sahabat Qur'an Early Childhood Tahfidz School comes with a unique tahfidzil Qur'an program using the At Tibyan method, especially using Arabic language media in its delivery. This research seeks to explain how Islamic Religious Education is provided at TAUD SAQU Jember along with the learning model used. This study uses qualitative research methods. The results of this study show the ability of TAUD SAQU Jember to integrate Tahfidz learning with the core of Islamic Education while maintaining PAIKEM. The learning model used is contextual learning (Contextual Teaching and Learning / CTL), which is adapted to the needs and conditions of students in the Jember area. TAUD SAQU's focus on tahfidz with At Tibyan and Tahajji methods formulates the realization of Islamic Religious Education well. The implementation of At Tibyan is carried out in the form of formal and non-formal learning by integrating teaching methods tailored to the situation and conditions of TAUD SAQU and its main objectives.